2019
DOI: 10.1007/s42729-019-00137-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sequestered Organic Carbon and Its Pools Under Different Agricultural Land-Uses in the Semi-Arid Soils of South-Western Punjab, India

Abstract: This is a study of long-term impact of agricultural land-uses on soil organic carbon (SOC) sequestration, its depth-wise distribution among some selected carbon pools, and their contribution towards loss of C through mineralization as CO 2 to understand the present situation as well as to elucidate future strategies. Soil samples from croplands, horticultural lands, and uncultivated lands in semi-arid India (south-western Punjab) were assessed for basic physico-chemical properties, SOC, SOC stock, KMnO 4oxidiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 97 publications
2
7
0
Order By: Relevance
“…The POM consists of partially decomposed plant litter, and it acts as a substrate and center for soil microbial activity, a shortterm reservoir of nutrients, a food source for soil fauna, and loci for formation of water stable macroaggregates (Haynes 2005). The POM could be considered a larger contributor to total SOC as Mandal et al (2019) showed a high positive correlation between POM carbon and SOC. The MHA is a labile fraction of humic substances rich in N, S, and H, characterized by phenolic moieties derived from the lignin residues, involved in short-term nutrients cycling (Olk 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The POM consists of partially decomposed plant litter, and it acts as a substrate and center for soil microbial activity, a shortterm reservoir of nutrients, a food source for soil fauna, and loci for formation of water stable macroaggregates (Haynes 2005). The POM could be considered a larger contributor to total SOC as Mandal et al (2019) showed a high positive correlation between POM carbon and SOC. The MHA is a labile fraction of humic substances rich in N, S, and H, characterized by phenolic moieties derived from the lignin residues, involved in short-term nutrients cycling (Olk 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It could be due to the higher biomass of plants at below and above ground, recalcitrance of leaf litter and plant root biomass of natural forest trees (Jha et al, 2012). Among the cultivated LUSs, the greater amount of SOC in the horticultural land-use might be due to higher addition of plant biomass into the soil in the form of leaf litter residue as well as less disturbance compared to other LUSs (Mandal et al, 2020). Loss of , 1996;Meena et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…3). The regression analysis The agricultural LUS had reduced the SOC concentration by oxidation of labile fraction of organic matter due to intensive tillage practices and soil disturbances (Purakayastha et al, 2008;Mandal et al, 2020). A higher correlation among SOC and nitrogen and other soil nutrients suggested that the production and concentration of these nutrients were principally determined by the amount and quality of soil organic matter under different USs (Meena et al, 2018).…”
mentioning
confidence: 99%
“…Overall the higher proportion of macroaggregates was observed for CS 1 . This may be attributed to higher amount of organic carbon (Table 1) which affected the activity of soil fauna and also soil aggregation [34]. Macro-aggregate formation is linearly correlated with SOC content [27].…”
Section: Soil Aggregationmentioning
confidence: 99%